The high energy X-ray probe (HEX-P): sensitive broadband X-ray observations of transient phenomena in the 2030s - Brightman, Murray; Margutti, Raffaella; Polzin, Ava; Jaodand, Amruta; Hotokezaka, Kenta; Alford, Jason A. J.; Hallinan, Gregg; Kammoun, Elias; Mooley, Kunal; Masterson, Megan; Marcotulli, Lea; Rau, Arne; et al. (Frontiers in Astronomy and Space Sciences, 2024)
HEX-P is a probe-class mission concept that will combine high spatial resolution X-ray imaging (< 10 FWHM) and broad spectral coverage (0.2-80 keV) with an effective area superior to NuSTAR above 10 keV to enable revolutionary new insights into a variety of astrophysical problems, especially those related to compact objects, accretion and outflows. HEX-P will launch at a time when the sky is being routinely scanned for transient gravitational wave, electromagnetic and neutrino phenomena that will require the capabilities of a sensitive, broadband X-ray telescope for follow up studies. These include the merger of compact objects such as neutron stars and black holes, stellar explosions, and the birth of new compact objects. A response time to target of opportunity (ToO) observation requests of < 24 hours and a field of regard of 3π steradians will allow HEX-P to probe the accretion and ejecta from these transient phenomena through the study of relativistic outflows and reprocessed emission, provide unique capabilities for understanding jet physics, and potentially revealing the nature of the central engine.